1991
DOI: 10.1136/thx.46.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypercapnia and hypocapnia on respiratory resistance in normal and asthmatic subjects.

Abstract: The effects of hypercapnia and hypocapnia on respiratory resistance were studied in 15 healthy subjects and 30 asthmatic subjects. Respiratory resistance (impedance) was measured with the pseudo-random noise forced oscillation technique while the subjects rebreathed from a wet spirometer in a closed respiratory circuit in which end tidal carbon dioxide tension (Pco2) could be controlled. Hypercapnia was induced by partially short circuiting the carbon dioxide absorber, and hypocapnia by voluntary hyperventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 24 publications
0
53
3
Order By: Relevance
“…When NEWHOUSE et al [123], for example, raised the minute ventilation in five normal males to 30 L?min -1 and dropped the PA,CO 2 to 2.7-3.3 kPa (20-25 mmHg), mean inspiratory flow resistance increased by 133% and mean respiratory work increased by 68% when compared with a minute ventilation that yielded a PA,CO 2 of 6.0-6.7 kPa (45-50 mmHg). Similarly, VAN DEN ELSHOUT et al [124] examined asthmatic patients with impulse oscillometry and found that a 1.0-kPa (7.5-mmHg) fall in the end-tidal carbon dioxide tension led to a 13.2% increase in airway resistance and a 45% fall in airway reactance.…”
Section: Hypocapniamentioning
confidence: 98%
See 1 more Smart Citation
“…When NEWHOUSE et al [123], for example, raised the minute ventilation in five normal males to 30 L?min -1 and dropped the PA,CO 2 to 2.7-3.3 kPa (20-25 mmHg), mean inspiratory flow resistance increased by 133% and mean respiratory work increased by 68% when compared with a minute ventilation that yielded a PA,CO 2 of 6.0-6.7 kPa (45-50 mmHg). Similarly, VAN DEN ELSHOUT et al [124] examined asthmatic patients with impulse oscillometry and found that a 1.0-kPa (7.5-mmHg) fall in the end-tidal carbon dioxide tension led to a 13.2% increase in airway resistance and a 45% fall in airway reactance.…”
Section: Hypocapniamentioning
confidence: 98%
“…This response is potentially problematic in asthmatic patients because hypocapnia has been shown to adversely affect airway resistance [123][124][125][126]. When NEWHOUSE et al [123], for example, raised the minute ventilation in five normal males to 30 L?min -1 and dropped the PA,CO 2 to 2.7-3.3 kPa (20-25 mmHg), mean inspiratory flow resistance increased by 133% and mean respiratory work increased by 68% when compared with a minute ventilation that yielded a PA,CO 2 of 6.0-6.7 kPa (45-50 mmHg).…”
Section: Hypocapniamentioning
confidence: 99%
“…[4-81. Bronchoconstriction also occurs in animals when carbon dioxide tension is reduced acutely [9, 101. In humans, hyperventilation asthma has been recognized for at least half a century [ll] and an acute fall in end-tidal carbon dioxide (ETCO2) of 7.5 mmHg has also been shown to contribute to airway obstruction in asthmatic patients [12] and patients undergoing hyperventilation (mean PaCOz 30.4 mmHg) because of neurological injury [13]. In normal subjects, acute hypocapnia (PaCOz 20-25 mmHg) also causes a consistent increase in flow resistance during sustained voluntary hyperventilation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in blood gas tension can be another sources of influence on the airways. The fall in PCO 2 related to hypocapnia has bronchoconstrictive effects, but there is conflicting evidence on effects of hypercapnia and hypoxia~Si-mon, Zanaboni, & Nyhan, 1997;van den Elshout, van Herwaarden, & Folgering, 1991!. Recommendation. Continuous measurements of ventilation should be included in psychophysiological studies of mechanical lung function.…”
Section: Ventilationmentioning
confidence: 99%